The Dual Vocation of Parenthood and Professional Theology: How are we Doing? Where are we Headed? - Bourg, Florence Caffrey (Horizons, 2005)
This article focuses on an increasing trend—the attempt to combine responsibilities of parenthood and professional theology in a dual vocation. Today, many theologians are attempting to complete doctoral studies and earn tenure with young children in tow. Most likely, this will become the majority trend in the near future. How well is our profession adjusting to this significant demographic shift? This article compiles results of a survey of parent-theologians, covering family planning decisions, financial stability, attempts to balance work and leisure, and impact of parenthood on their work as theologians, as well as their suggestions for making the profession more conducive to this dual vocation.